A Tracer Study of AB Psychology Graduates’ Employment Outcomes for Batches 2017-2020: Effects of Pandemic and Bases for Program Enhancement - Balah, Khadiguia O. (International Journal of Humanities and Education Development (IJHED), 2023)
This study examined the employment outcomes of 53 AB Psychology graduates out of 98 from the University of Southern Mindanao in the Philippines between 2017 and 2020. The findings showed that 66.04% of the graduates secured full-time employment, with a majority working in private firms (50.94%) and government organizations (13.21%), mainly in Davao City. The most common job role for these graduates was an administrative assistant in human resources and related fields. Those who worked for themselves had an annual income of P100,000 or more, while overall incomes ranged from P100,000 to P200,000. The COVID-19 pandemic caused increased stress and difficulty in finding employment for graduates. Despite these challenges, the alumni appreciated the program's curriculum, extracurricular activities, interdisciplinary learning, and opportunities for gaining practical knowledge. Graduates aspiring to become licensed guidance counselors and psychologists pursued advanced degrees in psychology, such as MA in Guidance and Counseling or MS/MA in Psychology. The pandemic influenced the perspective of recent graduates regarding further education. This research highlights the importance of practical experience, interdisciplinary learning, and a curriculum that prepares students for the current job market challenges faced by AB Psychology graduates. To address the pandemic's impact on employment, it is crucial to implement program interventions like virtual internships, expand career counseling services, and establish connections with companies to increase job opportunities. Curriculum adjustments should also be made to meet evolving market demands and ensure graduates are ready for a changing labor market.